The effect of additive manufacturing on the initial High temperature oxidation properties of RE-containing FeCrAl alloys. (1st August 2021) - Gunduz, K. Ozgur; Visibile, Alberto; Sattari, Mohammad; Fedorova, Irina; Saleem, Saud; Stiller, Krystyna; Halvarsson, Mats; Froitzheim, Jan
Highlights: Kanthal AM100 and Kanthal AF were exposed at 900 and 1100 °C for 168 h in air. No difference in oxidation rate was observed owing to the additive manufacturing. The overall oxidation rate of AM100 is not affected by the anisotropy in the microstructure. The AM microstructure causes local oxide scale thickness variations. Abstract: The effect of additive manufacturing on the high temperature oxidation properties of FeCrAl materials was investigated. For this purpose, additively manufactured Kanthal AM100 cut parallel and perpendicular to the building direction and hot-rolled Kanthal AF as a reference were exposed to air at 900 and 1100 °C for 168 h. AM100 performed slightly better than AF in terms of mass gain. Nevertheless, an oxide scale with local differences in thickness formed on AM100 due to the bimodal grain structure of the underlying metal, which was composed of coarse-grained cuboidal repeating units (100 μm wide), separated by fine-grained rims.